2017
DOI: 10.17977/um022v2i22017p095
|View full text |Cite
|
Sign up to set email alerts
|

Pemberdayaan Nelayan Berbasis Pendidikan Ekonomi Dan Potensi Pesisir di Kabupaten Minahasa Utara

Abstract: AbstrakArtikel penelitian ini bertujuan melakukan analisis kebutuhan pemberdayaan nelayan tradisional pesisir di Kabupaten Minahasa Utara Propinsi Sulawesi Utara berbasis pada pendidikan ekonomi dan potensi pesisir. Penelitian ini menggunakan rancangan penelitian deskriptif kualitatif dengan menggunakan metode survey, observasi lapangan, wawancara dan Focus Group Discussion (FGD). Subjek penelitian adalah nelayan pesisir Minahasa Utara berjumlah 40 orang nelayan yang tersebar pada 3 kecamatan yaitu Kecamatan L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…This study answers the problems faced by the fishing community as in some previous studies [11], [25] by using savings and financing products. There are some problems [11] that also cannot be fully answered by this research, where IMFI only provides what members need without giving a form of productivity and independence towards members. IMFI should be able to play a role in encouraging the fishing community (especially fishing laborers) to foster entrepreneurial spirit or work productively apart from fish production.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This study answers the problems faced by the fishing community as in some previous studies [11], [25] by using savings and financing products. There are some problems [11] that also cannot be fully answered by this research, where IMFI only provides what members need without giving a form of productivity and independence towards members. IMFI should be able to play a role in encouraging the fishing community (especially fishing laborers) to foster entrepreneurial spirit or work productively apart from fish production.…”
Section: Discussionmentioning
confidence: 57%
“…Wantah [11] with some of his surveys revealed that fishing communities do not understand good and proper financial management. They also need better knowledge in processing fish products, fostering an entrepreneurial spirit, and financial freedom.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Social Security generally implemented in various forms of direct income allowances that are strictly related to taxation and income-maintenance policies (Zebua, Wildani, Lasefa, & Rahmad, 2017). Social security often includes various schemes to increase access to essential social services, such as health care, education, and housing (Wantah, 2017).…”
Section: Social Securitymentioning
confidence: 99%
“…Program pemberdayaan yang dilakukan adalah dalam bentuk pelatihan teknologi usaha, bantuan sarana penangkapan ikan dan perlengkapan usaha budi daya laut serta benih. Adanya program tersebut diharapkan usaha perikanan yang dilakukan oleh masyarakat dapat menjadi usaha yang layak dan dapat meningkatkan kesejahteraan (Widiarto, Musa, & Sumantadinata, 2013;Wantah, 2017). Menurut Hikmat (2006), program ini akan berhasil jika komunikasi program dapat berjalan secara efektif yang ditandai oleh kesesuaian antara aturan yang ditetapkan dengan pelaksanaannya di lapangan.…”
Section: Latar Belakangunclassified